2016
DOI: 10.1111/jcmm.12987
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis is a key mediator of enterocytes loss in intestinal ischaemia/reperfusion injury

Abstract: Cell death is an important biological process that is believed to have a central role in intestinal ischaemia/reperfusion (I/R) injury. While the apoptosis inhibition is pivotal in preventing intestinal I/R, how necrotic cell death is regulated remains unknown. Necroptosis represents a newly discovered form of programmed cell death that combines the features of both apoptosis and necrosis, and it has been implicated in the development of a range of inflammatory diseases. Here, we show that receptor‐interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 56 publications
2
46
2
Order By: Relevance
“…Growing evidence suggests that instead of blocking the inflammatory cascade directly, novel strategies focusing on cell necroptosis may hold greater promise for improving outcomes in organ injury . We and others previously reported that necroptosis can promote inflammatory injury and acts as a key modulator in the pathogenesis of intestinal I/R injury and transplant survival in donor kidney, lung, and heart . In addition, RIP1‐dependent necrosis is involved in the pathological manifestation of acetaminophen‐induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Growing evidence suggests that instead of blocking the inflammatory cascade directly, novel strategies focusing on cell necroptosis may hold greater promise for improving outcomes in organ injury . We and others previously reported that necroptosis can promote inflammatory injury and acts as a key modulator in the pathogenesis of intestinal I/R injury and transplant survival in donor kidney, lung, and heart . In addition, RIP1‐dependent necrosis is involved in the pathological manifestation of acetaminophen‐induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male Sprague‐Dawley rats (weighing 220‐250 g ) were obtained from the Animal Center of Sun Yat‐sen University (Guangzhou, China). The rats were anesthetized with pentobarbital (30 mg/kg, intraperitoneally) and the intestinal I/R model was established according to our previous research . Briefly, the small intestine was exteriorized with a 2‐cm midline laparotomy, and the superior mesenteric artery (SMA) was identified.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations